A guide to Microsoft Office 2000 : Troubleshooting and problem solving - Chase, Kate. (Course Technology, 2000)
Introduction to Microsoft Office 2000. Working with Microsoft Word 2000. Advanced solutions for Word 2000 problems. Troubleshooting and problem solving in Excel 2000...